The mechanism of action of kefir and its effect on the motility of breast and colorectal cancer cells. (c2013) - Khoury, Nathalie El (2016)
Kefir which is a fermented milk product originating from the Caucasus Mountains is gaining increasing popularity due to its attribution in preventing or curing many chronic diseases among them cancer. Previous studies have focused on the anti-tumoral activity of kefir in vivo yet not extensive studies have been performed to elucidate its mechanism of action. Till now kefir is known to modulate intestinal microbiota, modulate the activity of immune system cells, and suspected to induce apoptosis in cancer cells in vivo. Recent studies have focused on the direct effect of kefir cell-free fractions on cancer cells in vitro. Earlier work in our lab has shown that cell-free fractions of kefir have anti-proliferative and pro-apoptotic effect on Caco-2 and HT-29 colorectal adenocarcinoma cells. In this study, we aim to determine a possible mechanism of action of kefir and to study its effect on the motility of colorectal and breast cancer cell lines. Results from the reverse-transcription PCR experiment have shown that kefir decreases the expression of TGF-α and TGF-β1 in HT-29 cells in a dose dependent manner. An increase in the production of both cytokines is usually associated with neoplastic transformation. Western blot assay results confirmed the previously observed increase in apoptosis as it showed an increase in Bax:Bcl-2 expression upon kefir treatment. Also an increase in p53 independent-p21 expression was observed in HT-29 cells upon kefir treatment which would explain the anti-proliferative effect of kefir. Furthermore, results from the time-lapse movies, wound-healing, and invasion assays showed no effect on the motility of colorectal (Caco-2 and HT-29) as well as breast (MCF-7 and MB-MDA-231) cancer cells upon kefir treatment.